Religious Coping among Working Muslim Women in Yogyakarta, Indonesia - Malida Fatimah; Junanah Junanah; Andi Musthafa Husain (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
Being a working woman is challenging, often entailing multiple conflicts. Despite these challenges, working women effectively navigate through a range of religious coping mechanisms. This study explored the application of religious coping by working Muslim women in Yogyakarta, Indonesia when confronted with stress-inducing situations. This study employed a quantitative approach using a survey method. The participant pool comprised of 54 working Muslim women from several locations in Yogyakarta, Indonesia. The research instrument included a religious coping scale featuring five coping types: Doubt about God's power and love, self-reflection and hopeful thinking, coping with pressure to achieve life changes, forgiveness based on religion, and rituals. The findings indicate that working women employ four coping strategies to address the pressures they encounter. Notably, none of the working women selected Doubt for God's power and love. This suggests that all participants in the study held the belief that God consistently supports them in overcoming challenges in life, especially those stemming from managing multiple roles.